Penurunan Keluhan Nyeri Pada Lansia Dengan Terapi Akupresur Herbal Compress Ball - Yuli Ernawati (STIKES Wira Husada Yogyakarta, 2022)
Reducing pain complaints in the elderly with herbal compress ball acupressure therapy. Pain is a major problem in the nursing home population, if not resolved, it will affect the quality of life of the elderly. It is necessary to innovate pain reduction with herbal compress ball acupressure therapy. This community service aims to reduce pain complaints in the elderly using herbal compress ball acupressure therapy. The activity was carried out by providing acupressure herbal compress ball therapy. The service team prepared dry herbal preparations such as ginger, turmeric, kencur, and camphor. The preparation is wrapped in a round shape with a cloth and steamed for 5-10 minutes until warm. The warm preparations are then used to compress the parts of the body that the elderly feel sick/uncomfortable. After the compression is complete, the level of pain felt by the elderly is evaluated. A total of 10 elderly are known to complain of pain before therapy activities. Giving therapy showed 8 elderly experienced a decrease.